Evolution of mechanical properties of LAE442 magnesium alloy processed by extrusion and ECAP - Peter Minárik (Journal of Materials Research and Technology, 2015)
The dependence of the mechanical properties on the increasing number of ECAP passes was investigated in the LAE442 magnesium alloy. The substantial grain refinement resulting from thermomechanical processing caused increase of the yield tensile strength and the ultimate tensile strength. Moreover, the fracture mechanism changed after thermomechanical processing, which led to a higher elongation to fracture.